Cost‐effectiveness of secondary fracture prevention intervention for Medicare beneficiaries. Issue 12 (3rd August 2021) - Nayak, Smita; Singer, Andrea; Greenspan, Susan L.
Abstract: Background: Secondary fracture prevention intervention such as fracture liaison services are effective for increasing osteoporosis treatment rates, but are not currently widely used in the United States. We evaluated the cost‐effectiveness of secondary fracture prevention intervention after osteoporotic fracture for Medicare beneficiaries. Methods: An individual‐level state‐transition microsimulation model was developed to evaluate the cost‐effectiveness of secondary fracture prevention intervention compared with usual care for U.S. Medicare patients aged 65 and older who experience a new osteoporotic fracture. Patients who initiated pharmacotherapy and remained adherent were assumed to be treated for 5 years. Outcome measures included subsequent fractures, average lifetime costs, quality‐adjusted life‐years (QALYs), and incremental cost‐effectiveness ratios in 2020 U.S. dollars per QALY gained. The model time horizon was lifetime, and analysis perspective was payer. Results: Base‐case analysis results showed that the secondary fracture prevention intervention strategy was both more effective and less expensive than usual care—thus, it was cost‐saving. Model findings indicated that the intervention would reduce the number of expected fractures by approximately 5% over a 5‐year period, preventing approximately 30, 000 fractures for 1 million patients. Secondary fracture prevention intervention resulted in an average cost savings of $418 and an increase in QALYs of 0.0299 per patient over the lifetime; for 1 million patients who receive the intervention instead of usual care, expected cost savings for Medicare would be $418 million dollars. One‐way and probabilistic sensitivity analyses supported base‐case findings of cost savings. Conclusion: Secondary fracture prevention intervention for Medicare beneficiaries after a new osteoporotic fracture is very likely to both improve health outcomes and reduce healthcare costs compared with usual care. Expansion of its use for this population is strongly recommended.